POLUTION OF BASIC NATURAL RESOURCES WITH HAZARDOUS MATTERS - Pejanović, Ljubo (Economics of Agriculture, 2015)
The paper analyzes conceptual guidelines and a multidimensional approach to the thematic of agriculture as a land property with rich and available natural resources, which are characterized by their specifcs. Specifcs of natural resources are characterized by renewable and non-renewable contents without which life is impossible, and these basic contents are land, air and water. In addition, agrarians and agriculture have natural riches in their possession, out of which food for living creatures on the planet is produced. Natural resources are the contents of agrarians and with every pollution, and thus destruction of natural resources, it damages and destroys sustainability of both natural resources and the sustainability of agriculture with its content of living creatures and plants on which life and survival on this planet depend on. Any pollution, especially from hazardous substances and excessive treatment from the air and ground, causes damage, destruction and loss of life which is contained by living creatures and plant life, a prerequisite for sustainable development and the survival on Earth. The problem and aim of this paper is to point out and prove a phenomenon of the modern world, which poses a threat to the survival of natural resources, and thus life to living things and plant life on Earth. However, the aforementioned phenomenon is not a much known one, its only known to a shortlist of scientists and theoreticians, while the general public is not aware of the mentioned and doesnt even assume the consequences of the threat.